2002
DOI: 10.1046/j.1365-2672.2002.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth studies of potentially probiotic lactic acid bacteria in cereal-based substrates

Abstract: Aims:The overall growth kinetics of four potentially probiotic strains (Lactobacillus fermentum, Lact. reuteri, Lact. acidophilus and Lact. plantarum) cultured in malt, barley and wheat media were investigated. The objectives were to identify the main factors influencing the growth and metabolic activity of each strain in association with the cereal substrate. Methods and Results: All fermentations were performed without pH control. A logistic-type equation, which included a growth inhibition term, was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(115 citation statements)
references
References 38 publications
7
103
0
5
Order By: Relevance
“…With regards to the fermentation time, much longer is usually needed than during standard cow milk yogurt production, since potential probiotic bacteria (type of bacteria currently chosen to develop these foodstuffs due to the added value on the final product) have more complex nutritional requirements (Severson, 1998), especially when growing in vegetable matrices. The reported fermentation times have been found to be around 16-24 h if no growth enhancers are used in the formulation (Dimitris Charalampopoulos & Pandiella, 2010;D Charalampopoulos, Pandiella, & Webb, 2002;Coda, Rizzello, & Gobbetti, 2010;Correa, Castro, & Saad, 2008;Blaiotta, Di Capua, Coppola, & Aponte, 2012;Cui, Chen, Wang, & Han, 2013;Gokavi et al, 2005;Gupta, Cox, & Abu-Ghannam, 2010;Martensson, Oste, & Holst, 2002). The fermentation procedure finishes when the pH value of milks reaches 4.2-4.5.…”
Section: Processing Of Fermented Vegetable Milkmentioning
confidence: 99%
“…With regards to the fermentation time, much longer is usually needed than during standard cow milk yogurt production, since potential probiotic bacteria (type of bacteria currently chosen to develop these foodstuffs due to the added value on the final product) have more complex nutritional requirements (Severson, 1998), especially when growing in vegetable matrices. The reported fermentation times have been found to be around 16-24 h if no growth enhancers are used in the formulation (Dimitris Charalampopoulos & Pandiella, 2010;D Charalampopoulos, Pandiella, & Webb, 2002;Coda, Rizzello, & Gobbetti, 2010;Correa, Castro, & Saad, 2008;Blaiotta, Di Capua, Coppola, & Aponte, 2012;Cui, Chen, Wang, & Han, 2013;Gokavi et al, 2005;Gupta, Cox, & Abu-Ghannam, 2010;Martensson, Oste, & Holst, 2002). The fermentation procedure finishes when the pH value of milks reaches 4.2-4.5.…”
Section: Processing Of Fermented Vegetable Milkmentioning
confidence: 99%
“…Rich and complex media, like MRS (De Man et al, 1960) or M17 (Terzaghi and Sandine, 1975) (Kurbanoglu, 2004), corn steep liquor (Cornelius et al, 1996;Marcela et al, 2016), whey protein hydrolysates (Mc Comas and Gilliland, 2003;Watanabe et al, 2004), malt sprout extract, casein hydrolysates (Vahvaselkä and Linko, 1987;Chiarini et al, 1992;Horáčková, 2014), baker's yeast cells (Altaf et al, 2007), vegetal substrates (Gardner et al, 2001;Nancib et al, 2001;Charalampopoulos et al, 2002;Djeghri-Hocine et al, 2006;Djeghri-Hocine et al, 2007a), sugarcane juice (Preeti et al, 2016), Palmyra palm jaggery (Reddy Tadi et al, 2017), and de-lipidated egg yolk (DjeghriHocine et al, 2007b). The most efficient nitrogen source seems to be yeast extract (Aeschlimann and Von Stokar, 1990;Arasaratnam et al, 1996;Göksungur and Gűvenç, 1997;Guha et al, 2013;Vethakanraj et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous cereal-based products in the world require a lactic fermentation, often in association with yeast or molds. Cereals are good substrates for the growth of probiotic strains and due to the presence of non-digestible components of the cereal matrix may also serve as prebiotics [114,115]. Due to the complexity of cereals, a systematic approach is required to identify the factors that enhance the growth of probiotic in cereals [116].…”
Section: Cereal-based Probiotic Productsmentioning
confidence: 99%
“…Also the addition of sweeteners aspartame, sodium cyclamate, saccharine and Huxol (12% cyclamate and 1.2% saccharine) had no effect on the dynamics of the fermentation process and on the viability of the starter culture during product storage [93]. Charalapompoulos and others have done experiments with different cereals to determine the main parameters that need to be considered in the growth of probiotic microorganisms, defining them as follows: the composition and processing of cereal grains, the substrate formulation, the growth capability and productivity of the starter culture, the stability of the probiotic strain during storage, the organoleptic properties and the nutritional value of the final product [114]. They reported that many cereals supported the growth of probiotics with some differences.…”
Section: Cereal-based Probiotic Productsmentioning
confidence: 99%